ChemInform Abstract: Linear Dialdehydes as Promising Substrates for Aminocatalyzed Transformations. Issue 14 (April 2015) - Kumar, Indresh; Ramaraju, Panduga; Mir, Nisar A.; Singh, Anoop
Abstract: Review: 54 refs.